Laparoscopic Resection of T4 Colon Cancers. Issue 1 (January 2015) - Shukla, Parul J.; Trencheva, Koiana; Merchant, Chetan; Maggiori, Leon; Michelassi, Fabrizio; Sonoda, Toyooki; Lee, Sang W.; Milsom, Jeffrey W.
<x xml:space="preserve">Abstract</x> BACKGROUND: Laparoscopic surgical treatment of T4 cancers remains a concern that is mostly associated with technical feasibility, high conversion rate, inadequate oncologic clearance, and surgical outcome. OBJECTIVE: The purpose of this work was to evaluate the short- and long-term clinical and oncologic outcomes after laparoscopic and open surgeries for T4 colon cancers. DESIGN: This was a retrospective study of patients with T4 colon cancer without metastasis (M0) who had laparoscopic or open surgery from 2003 to 2011. SETTING: The study was conducted at a single institution. PATIENTS: A total of 83 patients with pT4 colon cancer were included. MAIN OUTCOME MEASURES: R0 resection rate, morbidity and mortality within 30 postoperative days, overall survival, and disease-free survival were measured. RESULTS: Laparoscopic surgery was performed on 61 and open surgery on 22 patients. The groups were similar in overall staging (p = 0.461), with 35 (42%) of the patients at stage 2 and 48 (58%) at stage 3. A complete R0 resection was achieved in 61 (100%) of the patients who underwent laparoscopic surgery and in 21 (96%) of the patients who underwent open surgery (p = 0.265). The average number of lymph nodes harvested was 21 in the laparoscopic group and 24 in the open group (p = 0.202). Thirty-day morbidity rate was similar between the groups (p = 0.467), and the mortality rate was 0. The length of hospital and postsurgical stay was significantly shorter in the laparoscopic group (p = 0.002 and p = 0.008). The 3-year overall survival rates between the groups were 82% (range, 71%–93%) for patients who underwent laparoscopic surgery and 81% (range, 61%–100%) for those who underwent open surgery (p = 0.525), and disease-free survival was 67% (range, 54%–79%) for laparoscopic surgery and 64% (range, 43%–86%) for open surgery (p = 0.848). The follow-up time was 40 ± 25 in months in the laparoscopic group and 34 ± 26 months in the open surgery group (p = 0.325). LIMITATIONS: This was a retrospective study at a single institution. CONCLUSIONS: The study shows that laparoscopic surgery is feasible in T4 colon cancers. With comparable clinical and oncologic outcomes, this study suggests that laparoscopy may be considered as an alternative approach for T4 colon cancers with the advantage of faster recovery (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A156).